Adaptive Multi-Observer Design for Systems with Unknown Long Input Delay. Issue 18 (2019) - Novella-Rodrìguez, David F.; Witrant, Emmanuel; Muro-Cuéllar, Basilio del; Márquez-Rubio, Juan F.
Abstract: This paper deals with the problem of stabilization of systems with a constant delay in the actuator. The time-delay is unknown and can be considerably long, involving an interesting challenge from the control point of view. The proposed control scheme is based on a set of infinite dimensional observers with an adaptive time-delay estimation. The convergence of the observers is studied considering the time-varying delays introduced by the delay estimation. A stability analysis of the closed-loop control system is provided. The proposed observer-based controller is tested by means of numerical simulation, considering an unstable plant.